Gene editing of DNAH11 restores normal cilia motility in primary ciliary dyskinesia. Issue 4 (4th January 2016) - Lai, Michele; Pifferi, Massimo; Bush, Andrew; Piras, Martina; Michelucci, Angela; Di Cicco, Maria; del Grosso, Ambra; Quaranta, Paola; Cursi, Chiara; Tantillo, Elena; Franceschi, Sara; Mazzanti, Maria Chiara; et al.
Abstract : Background: Primary ciliary dyskinesia (PCD) is a rare autosomal recessive genetic disorder characterised by dysfunction of motile cilia. Ciliary dysmotility causes poor mucociliary clearance and leads to impairment of pulmonary function and severe respiratory infections. PCD has no specific therapy. With the aim to permanently restore gene function and normalise ciliary motility, we used gene editing to replace mutated with wild-type sequence in defective cells. Methods: The target gene was dynein heavy chain 11 ( DNAH11 ), an essential component of ciliary structure. Airway ciliated cells were collected from two patients with PCD with DNAH11 nonsense mutations and altered ciliary beating and pattern. Repair of the genetic defect was performed ex vivo by site-specific recombination using transcription activator-like effector nucleases (TALENs). Results: In an epithelial cell line engineered to contain the DNAH11 target site, TALENs cleaved over 80% of the mutated DNAH11 sequence and replaced the mutated sequence with wild-type sequence in about 50% of cells. In airway ciliated cells of patients with PCD, site-specific recombination and normalisation of ciliary beating and pattern occurred in 33% and 29% of cells, respectively. Conclusion: This study demonstrates that gene editing can rescue ciliary beating ex vivo, opening up new avenues for treating PCD.